The Association of Serum Sodium Levels with Intraventricular Hemorrhage in Preterm Infants: A Prospective Longitudinal Study from Pakistan - Bhanbhro, Bakhtiar Ahmed; Bharo, Mumtaz Ali; Baloach, Kamran Ali Shahani; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the association of hypernatremia with intraventricular haemorrhage in preterm infants in a local setting.Study Design: Prospective longitudinal study.Place and Duration of Study: Neonatal Intensive Care Units (NICU), Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat Khaipur Mirs from Sep 2018 to Mar 2020.Methodology: All the infants with the gestational age of